Prognostic markers in congenital diaphragmatic hernia: Left ventricular diameter and pulmonary hypertension. Issue 2 (23rd January 2018) - Karpuz, Derya; Giray, Dilek; Celik, Yalcin; Hallioglu, Olgu
Abstract: Background: The aim of this study was to investigate whether the outcome of congenital diaphragmatic hernia (CDH) in newborns can be predicted using left ventricular (LV) diameter and estimated pulmonary artery pressure. Methods: Patients in the newborn unit in 2012–2016 were screened retrospectively. Echocardiographic measurements of 35 patients with isolated left lateral CDH and 27 healthy newborns were compared in the first 24 h of life. Results: Mean LV end‐diastolic diameter (LVEDD) and end‐systolic diameter (LVESD), and LV ejection fraction were significantly lower in the CDH group. Moreover, tricuspid regurgitation (TR) and pulmonary regurgitation (PR) were significantly higher than in the controls ( P < 0.001). Six CDH patients died within the next 40 days after birth. Mean LVEDD and LVESD were significantly lower in the CHD patients who died compared with those who were discharged ( P < 0.001, P = 0.016). Also, mean TR and PR ( P < 0.001) and the frequency of pulmonary hypertension (PH; P = 0.001) were significantly higher in these patients. On receiver operating characteristic analysis of the CDH non‐survivors, LVEDD < 11 mm (sensitivity, 100%; 95%CI: 87.9–100; specificity, 100%; 95%CI: 54.1–100) and TR > 3.5 m/s (sensitivity, 89.66%; 95%CI: 72.6–97.7; specificity, 100%; 95%CI: 54.1–100) were associated with poor prognosis. Conclusions: Decrease in LVEDD and presence of PH are associated with poor prognosis. Also, PH was associated with mortality in CDH patients. Thus, outcome may be predicted on careful echocardiographic evaluation of the LV diameters and pulmonary pressure.